E-Commerce A Strategic Tool for Indian Readymade Garment Exporters To Leverage Their Positions in International Markets - Valecha, Deepesh (2007)
Electronic commerce is the engine that drives the new world economy. The endless benefits reaped from it by the developed countries are well known but its role in developing countries like India is not known. The garment industry of India is one of the biggest sectors and contributes a major part in the national income and generation of foreign exchange. This paper attempts to investigate the current position of e commerce in the garment industry in India through a sample of 20 firms. The aim is to find out the extent to which garment exporters are using the e commerce applications, the ways in which these applications are being used, the benefits exporters are able to reap form it, the problems that they face and the steps that need to be taken to catch up with the pace of e commerce. The results suggested that the firms either fail to or are not willing to implement e commerce and currently they are using not even 1% of what we call Internet based B2B e commerce. There were different barriers found in the implementation of e commerce in the garment industry. I tried to analyze the current situation, and presented the reasons for lagging behind. Later I have discussed recommendations based on the findings of the research. The main problem faced in the research was that there has been very less research on the effects of e commerce in India till now and absolutely no research on the effects of e commerce on exporters in India.